Individualisation of Migration from the East? Comparison of Different Socio-Demographic Groups and their Migration Intentions - Saar, Maarja (Studies of Transition States and Societies, 2016)
Recent studies on Eastern European migration argue that moving for self-development reasons is becoming increasingly common among this group. Furthermore, it is suggested that migration from the East is becoming individualised and less dependent on social surroundings. Nevertheless, most such results rely on interviews conducted among certain social groups, such as the young and highly skilled. Hence, the comparison between different social groups and their motivations is rarely provided and, therefore, the claims about increased individualisation might be premature. This article uses the Estonian Household Module Survey, including responses from 620 Estonians intending to migrate, to evaluate if migration flows are indeed becoming more individualised and less dependent on social surroundings. Using cluster analysis, three different groups — self-development, economic and life quality migrants — are formed, which are then tested using regression analysis to check for the influence of socio-demographic variables. The article concludes that socio-demographic variables such as gender, age, ethnicity, family status and socio-economic status are still relevant for migration intentions. Indeed, a new group of Eastern European migrants, mainly oriented towards self-development, is emerging; however, it is small and consists mostly of young, Estonian-speaking females. The results complicate the notions of free mobility and liquid migration from Eastern Europe and illustrate that there is a need to pay attention to the increasing group differences in these societies.